PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP DISIPLIN KERJA (STUDI KASUS PNPM MANDIRI PERDESAAN PERTANIAN DI PROVINSI PAPUA DAN PROVINSI PAPUA BARAT) - Sihombing, Tulus P.J. (Operations Excellence: Journal of Applied Industrial Engineering, 2016)
Abstract. Field Program has strategic role in improving the income poor farmers in the land of Papua. Work motivation, working environment and work discipline will help escort in program activities. Research to know the influence of motivation of work, and workplace against discipline of work. Study on National Society Empowerment Program Rural Agriculture in Papua Province and West Papua Province. Independent variables consists work motivation and Work environement, with work discipline as dependent variable. The sampling method used is saturated and sample of respondents who provide the answer as many as 58 people of respondents. The method of analysis used in this study is multiple linear regression. The research results showed indicate the presence of the positive significant effect or influence of working environment in partial against discipline of work. The two of variables consits work motivation and work environment jointly showed significant effect to work discipline. Work environment give stir the very great work discipline. While work motivation by partial not influence to work discipline work. Keywords: Motivate The Job, Environmental Work and Discipline Work